Development of a novel chimeric lysin to combine parental phage lysin and cefquinome for preventing sow endometritis after artificial insemination - Xin-xin Li; Zi-qiang Hong; Zhi-xuan Xiong; Li-wen Zhang; Shuang Wang; Pan Tao; Pin Chen; Xiang-min Li; Ping Qian (Veterinary Research)
Abstract Sow endometritis is usually caused by multiple species of pathogenic bacteria. Numerous isolates from endometritis patients have developed antimicrobial resistance. Thus, novel antibacterial agents and strategies to combat endometritis are needed. A total of 526 bacteria, including Staphylococcus spp. (26.3%), Streptococcus spp. (12.3%), E. coli (28.9%), Enterococcus spp. (20.1%), Proteus spp. (9.5%), and Corynebacterium spp. (2.8%), were isolated from sows with endometritis. We constructed a novel chimeric lysin, ClyL, which is composed of a cysteine- and histidine-dependent amidohydrolase/peptidase (CHAP) catalytic domain from the phage lysin LysGH15 and a cell wall-binding domain (CBD) from the prophage lysin Lys0859. The activities of ClyL and Lys0859 were most pronounced for the Staphylococcus and Streptococcus strains isolated from sow endometritis and bovine mastitis, respectively. ClyL and Lys0859 were combined to create a phage lysin cocktail, which demonstrated a synergistic effect against the coinfection of Staphylococcus and Streptococcus in vitro and in vivo. Furthermore, the combination of phage lysin cocktail and cefquinome had a synergistic bactericidal effect on boar semen that did not influence the activity of sperm. Remarkably, the incidence rate of sow endometritis was 0% (0/7) when the combination of phage lysin cocktail and cefquinome was used in semen via artificial insemination compared with 50% (3/6) when PBS was administered. Overall, the administration of a phage lysin cocktail and cefquinome in semen via artificial insemination is a promising novel strategy to prevent sow endometritis after artificial insemination.